Influence of Impurities on the Radiation Response of the TlBr Semiconductor Crystal - Robinson Alves dos Santos; Carlos Henrique de Mesquita; Júlio Batista Rodrigues da Silva; Caue de Melo Ferraz; Fabio Eduardo da Costa; João Francisco Trencher Martins; Roseli Fernandes Gennari; Margarida Mizue Hamada (Advances in Materials Science and Engineering)
Two commercially available TlBr salts were used as the raw material for crystal growths to be used as radiation detectors. Previously, TlBr salts were purified once, twice, and three times by the repeated Bridgman method. The purification efficiency was evaluated by inductively coupled plasma mass spectroscopy (ICP-MS), after each purification process. A compartmental model was proposed to fit the impurity concentration as a function of the repetition number of the Bridgman growths, as well as determine the segregation coefficients of impurities in the crystals. The crystalline structure, the stoichiometry, and the surface morphology of the crystals were evaluated, systematically, for the crystals grown with different purification numbers. To evaluate the crystal as a radiation semiconductor detector, measurements of its resistivity and gamma-ray spectroscopy were carried out, using 241Am and 133Ba sources. A significant improvement of the radiation response was observed in function of the crystal purity.